Favorable ecological circumstances promote life expectancy in chimpanzees similar to that of human hunter-gatherers. Issue 105 (April 2017) - Wood, Brian M.; Watts, David P.; Mitani, John C.; Langergraber, Kevin E.
Abstract: Demographic data on wild chimpanzees are crucial for understanding the evolution of chimpanzee and hominin life histories, but most data come from populations affected by disease outbreaks and anthropogenic disturbance. We present survivorship data from a relatively undisturbed and exceptionally large community of eastern chimpanzees ( Pan troglodytes schweinfurthii ) at Ngogo, Kibale National Park, Uganda. We monitored births, deaths, immigrations, and emigrations in the community between 1995 and 2016. Using known and estimated ages, we calculated survivorship curves for the whole community, for males and females separately, and for individuals ≤2 years old when identified. We used a novel method to address age estimation error by calculating stochastic survivorship curves. We compared Ngogo life expectancy, survivorship, and mortality rates to those from other chimpanzee communities and human hunter-gatherers. Life expectancy at birth for both sexes combined was 32.8 years, far exceeding estimates of chimpanzee life expectancy in other communities, and falling within the range of human hunter-gatherers (i.e., 27–37 years). Overall, the pattern of survivorship at Ngogo was more similar to that of human hunter-gatherers than to other chimpanzee communities. Maximum lifespan for the Ngogo chimpanzees, however, was similar to that reported at other chimpanzee research sites and was less than that of human-hunter gatherers. The absence of predation by large carnivores may contribute to some of the higher survivorship at Ngogo, but this cannot explain the much higher survivorship at Ngogo than at Kanyawara, another chimpanzee community in the same forest, which also lacks large carnivores. Higher survivorship at Ngogo appears to be an adaptive response to a food supply that is more abundant and varies less than that of Kanyawara. Future analyses of hominin life history evolution should take these results into account.